18v-(8v-7)=67

Simple and best practice solution for 18v-(8v-7)=67 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 18v-(8v-7)=67 equation:


Simplifying
18v + -1(8v + -7) = 67

Reorder the terms:
18v + -1(-7 + 8v) = 67
18v + (-7 * -1 + 8v * -1) = 67
18v + (7 + -8v) = 67

Reorder the terms:
7 + 18v + -8v = 67

Combine like terms: 18v + -8v = 10v
7 + 10v = 67

Solving
7 + 10v = 67

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + -7 + 10v = 67 + -7

Combine like terms: 7 + -7 = 0
0 + 10v = 67 + -7
10v = 67 + -7

Combine like terms: 67 + -7 = 60
10v = 60

Divide each side by '10'.
v = 6

Simplifying
v = 6

See similar equations:

| 3/5w-7/3=-5/2 | | -2y+24=6 | | -4(n+2)=(n-4) | | 1/2×12 | | 10m^2-21m-6=0 | | 6(2x-5)=4(x+8) | | 25=x-(3x+5) | | X-1/3-2/3 | | x^2+y-10x+2y+17=0 | | f(-3)=-3+9 | | ×-1/3-2/3 | | 5-6p=-79 | | x^7+x^4-9x^3=9 | | (420)6/180= | | (420)6/180=x | | 25+4m+25+4m=159 | | X/28=2/10 | | 6(5x-3)=12 | | (3/5w)-(5/3)=(-7/4) | | 1-x=4+17 | | 5ab-3ab+ab= | | m-(5)-(-12m)= | | -3/10=-31/20*10/3u | | B/13=3/13 | | x/4=3/× | | x+x+0.05+x+0.05+1.06=8.75 | | (-2)*(6)= | | 9=x/6 | | -14=-29 | | -(5k-7)=-4k+10 | | (x-6)(x+4)=(3-x)(8-x) | | 6+x^2=14 |

Equations solver categories